Pemberian Nafkah Suami Terpidana bagi Keluarga (Studi Kasus di Lembaga Pemasyarakatan Kelas II A Kendari) - Batmang Batmang (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
The purpose of this study was to determine the provision for the family convicts when left by the head of the family in prison, in order to find a solution for the family convicts economic difficultiesafter being left by the head of the family based on the perspective of a review of Islamic law and thelegislation relating to the liabilities convict husband in providing a living for the family. This study useskualitatif- sociological approach. The data collection is done by observation, interviews related to the reality of the fulfillment of family income. The results showed that the convict husband living on the family is still given according to ability. Overview of Islamic law and the laws pertaining to the obligations of convicts husband in providing the family income is confirmed in QS. Al-Baqarah 2: 233, legislation duty of the husband to provide a living stated in Law No. 1 of 1974 on marriage Chapter VI of Article 30 to Article 34 and the Islamic Law Compilation (KHI) CHAPTER XII Article 77 to Article 84.